Expanding the Evidence of a Semi-Dominant Inheritance in GDF2 Associated with Pulmonary Arterial Hypertension - Natalia Gallego (MDPI AG, 2021)
Pulmonary arterial hypertension (PAH) sometimes co-exists with hereditary hemorrhagic telangiectasia (HHT). Despite being clinically diagnosable according to Curaçao criteria, HHT can be difficult to diagnose due to its clinically heterogenicity and highly overlapping with PAH. Genetic analysis of the associated genes ACVRL1, ENG, SMAD4 and GDF2 can help to confirm or discard the presumptive diagnosis. As part of the clinical routine and to establish a genetic diagnosis, we have analyzed a cohort of patients with PAH and overlapping HHT features through a customized Next Generation Sequencing (NGS) panel of 21 genes, designed and validated in-house. We detected a homozygous missense variant in GDF2 in a pediatric patient diagnosed with PAH associated with HHT and a missense variant along with a heterozygous deletion in another idiopathic PAH patient (compound heterozygous inheritance). In order to establish variant segregation, we analyzed all available family members. In both cases, parents were carriers for the variants, but neither was affected. Our results expand the clinical spectrum and the inheritance pattern associated with GDF2 pathogenic variants suggesting incomplete penetrance and/or variability of expressivity with a semi-dominant pattern of inheritance.